2017
DOI: 10.1038/s41598-017-13672-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Phthalate Exposure on Thyroid Hormone Concentrations Beginning at The Embryonic Stage

Abstract: Limited studies have consistently shown an association of phthalates exposure with thyroid hormones (THs) in pregnant women. However, it remains unknown on which specific phthalates can affect THs and whether any effects could differ by gestational age. In the present study, we investigated associations between serum concentrations of phthalate monoesters [monoethyl phthalate (MEP), mono-(n + iso)-butyl phthalate (MBP) and mono(2-ethylhexyl) phthalate (MEHP)] and THs [thyroid-stimulating hormone (TSH), total t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…2004 ). Prenatal exposure to phthalates has been associated with changes in circulating thyroid hormone and low thyroid function in pregnant women, including during early pregnancy ( Gao et al. 2017 ; Johns et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2004 ). Prenatal exposure to phthalates has been associated with changes in circulating thyroid hormone and low thyroid function in pregnant women, including during early pregnancy ( Gao et al. 2017 ; Johns et al.…”
Section: Discussionmentioning
confidence: 99%
“…2009 ; Bonefeld-Jørgensen et al. 2007 ; Gao et al. 2017 ; Ghisari and Bonefeld-Jorgensen 2009 ; Lyche et al.…”
Section: Introductionunclassified
“…In the U.S. children (N = 1493) of 6–15 years of age, with reported attention deficit disorder (ADD) or Learning Disability (LD), it has been demonstrated an association between phthalates and these disorders, with a prevalence in girls than boys [ 139 ]. The mechanism underlying this effect may rely on the disruption of thyroid system during pregnancy [ 140 , 141 ].…”
Section: Toxicological Aspects and Human Health Effectsmentioning
confidence: 99%
“…Regarding possible interference from phthalates during pregnancy, the majority of studies have reported a negative correlation between levels of several metabolites and THs, particularly free and total T4 and free T3 levels, and a positive correlation with TSH levels, and these effects may depend on the timing of exposure during gestation (Huang et al 2007, Johns et al 2015, Yao et al 2016, Gao et al 2017. However, other studies have shown very different results, with an inverse association with TSH and a positive association with free and total T4 levels (Huang et al 2007, Johns et al 2015, Yao et al 2016, Gao et al 2017. Regarding phthalate exposure and neonatal thyroid status, some studies have shown a correlation between phthalate levels and TH levels in newborns; a Dutch prospective cohort detected changes in free T4 levels in girls but not in boys (de Cock et al 2014), and a study in Taiwan found an association of phthalate exposure with reduced levels of THs in young children (Huang et al 2017a,b).…”
Section: Plasticizersmentioning
confidence: 99%